A Review of Electrocatalytic Reduction of Dinitrogen to Ammonia under Ambient Conditions. Issue 22 (21st May 2018) - Cui, Xiaoyang; Tang, Cheng; Zhang, Qiang
Abstract: The production of ammonia (NH3 ) from molecular dinitrogen (N2 ) under mild conditions is one of the most attractive topics in the field of chemistry. Electrochemical reduction of N2 is promising for achieving clean and sustainable NH3 production with lower energy consumption using renewable energy sources. To date, emerging electrocatalysts for the electrochemical reduction of N2 to NH3 at room temperature and atmospheric pressure remain largely underexplored. The major challenge is to achieve both high catalytic activity and high selectivity. Here, the recent progress on the electrochemical nitrogen reduction reaction (NRR) at ambient temperature and pressure from both theoretical and experimental aspects is summarized, aiming at extracting instructive perceptions for future NRR research activities. The prevailing theories and mechanisms for NRR as well as computational screening of promising materials are presented. State‐of‐the‐art heterogeneous electrocatalysts as well as rational design of the whole electrochemical systems for NRR are involved. Importantly, promising strategies to enhance the activity, selectivity, efficiency, and stability of electrocatalysts toward NRR are proposed. Moreover, ammonia determination methods are compared and problems relating to possible ammonia contamination of the system are mentioned so as to shed fresh light on possible standard protocols for NRR measurements. Abstract : Recent progress in electrochemical nitrogen reduction reaction (NRR) at ambient temperature and pressure is reviewed from both theoretical and experimental aspects, focusing on state‐of‐the‐art heterogeneous electrocatalysts as well as rational design of the whole electrochemical systems for NRR. Promising strategies to boost NRR and to suppress/circumventthe hydrogen evolution reaction are discussed. Moreover, methods and precautions for the determination of ammonia are also involved to invoke future standard protocols for NRR measurements.